The impact of accountability on judgments of ethical decisions - Silva, V. H. (2011)
When appraising the ethicality of another person’s decision, individuals tend to take the valence of the consequences as a basis for their judgment. Specifically, an ethically dubious decision tends to be more acceptable when the consequences are displayed as positive. This paper discusses the results of observation of the effect of accountability to unknown third parties on this process. Results from an experimental study (N=251) indicate that individuals under process accountability tend to be more severe in their judgment of the acceptability of other’s ethically dubious decisions than the non-accountable ones and those who are under outcome accountability, but only when the decision’s consequences are displayed as positive or neutral. This effect does not occur when the consequences of the decision are seen as negative. In this case, people tend to consider the decision ethically unacceptable, regardless of whether or not they’re held accountable to unknown constituents. These tendencies are independent of the individual differences in the propensity to make cognitive effort in problem analysis. Results are discussed from the perspective of decision making in organizations, and their possible relevance to the establishment of mechanisms to increase the scrutiny of the ethicality of decisions.